Perlakuan Pajak Penghasilan bagi Yayasan Pendidikan - Tansuria, Billy Ivan (JBE (Journal of Business and Economics); Volume 8 No.1, 2009 JBE UNKLAB, 2009)
Some people have the notion that income tax should not be imposed on educational institutions, due to their non-profit state. Nevertheless, based on current regulation of income tax (Law of the Republic of Indonesia Number 36 of 2008 concerning Income Tax/UU No.36/2008), it is clearly and explicitly stated that edu-cational institutions are subjected to income tax, whenever there is a profit. The government, however, has special consideration and treatment on calculating the profit of Indonesian educational institutions so as to use the foresaid fund (the remaining profit) for quality improvement of the means and facilities of education in Indonesia. The objective of this paper is to discuss the reasons why income tax can be imposed on educational institutions based on the current regulation and how the educational institutions are treated differently regarding the income tax of profit on yearly basis.